Variations in the chemical composition of the solution extracted from a Latosol under fertigation with vinasse - Francisco, João; Folegatti, Marcos; Silva, Leonardo; Silva, Jonathas; Diotto, Adriano (Revista Ciência Agronômica, 2016)
The aim of this work was to evaluate the change in electrical conductivity and pH of a soil solution and its composition, with regard to the levels of nitrate and potassium, in a Latosol cultivated with pineapple and subjected to applications of different levels of vinasse. The experiment was conducted in a greenhouse at the Department of Biosystems Engineering of ESALQ/USP. The treatments comprised the application of five levels of vinasse: T1 - 0 m3 ha-1, T2 - 231 m3 ha-1, T3 - 347 m3 ha-1, T4 - 462 m3 ha-1, and T5 - 578 m3 ha-1. Application was every 20 days, using a localised irrigation system with emitters having a nominal flow rate of 4 L h-1 and spaced 0.40 m apart. The applied doses of vinasse were calculated by following the recommendations of CETESB standard P4.231, so that treatment T4 would supply the demand of the pineapple plant for potassium. The solution was collected by means of porous capsule extractors at 30, 120 and 210 days from the start of vinasse application. It was found that increases in the volume of the applied levels resulted in greater values for the electrical conductivity of the soil (ECs) and in the concentration of potassium (K) and nitrate (NO3), with higher values being obtained in the 0.20 m layer. The results demonstrated that pH decreased with increases in the vinasse being applied.